Factors Affecting the Iran Commercial Bank Credit with emphasis On non-performing loans - siavash golzarian pour; hasan golmoradi; mahdi esmaili (پژوهش‌های برنامه و توسعه)
AbstractToday, one of the most important problems facing the banking system of the country is the increase in non-performing loans, consequently reduction of liquidity, disruption in the allocation of resources and ultimately a decline in bank profit. This study examines the factors (such as the economic growth rate, the average interest rate and etc.) affecting lending for 17 Iran commercial banks in 1388-1395. In the study, the ratio of loans to total assets was used as the dependent variable. The independent variables are deposits ratio, capital ratio, the ratio of non-performing loan, The average interest rate on deposit and loan, bank size, inflation rate, required reserve ratio and the rate of economic growth. In addition, the statistical method and software used in this research is panel data and Eviews8 respectively. The results indicate a negative impact of NPL, liquidity ratio and average interest rate on lending and also positive impact of deposits ratio and economic growth rate. Keywords: Bank credit, non-performing loan, commercial banks.JEL Classification: E51,G21